Device-based physical activity levels among Finnish adolescents with functional limitations. Issue 1 (January 2019) - Ng, Kwok W.; Rintala, Pauli; Husu, Pauliina; Villberg, Jari; Vasankari, Tommi; Kokko, Sami
Abstract: Background: Monitoring physical activity among young adolescents with disabilities is a top academic priority. People with disabilities are a diverse group with various abilities in different human functioning. Therefore, we used a novel approach through functional limitations as a marker for disabilities and examined physical activity levels. Objective: To investigate the levels and differences in light (LPA) and moderate-to-vigorous (MVPA) intensity physical activity between young adolescents with and without functional limitations. Methods: The study included young adolescents (n = 1436) aged 11–15 years olds who attended general schools that were part of the 2016 Finnish School-aged Physical Activity (FSPA) study. PA levels were measured by hip-worn accelerometers during seven consecutive days. The data were disaggregated by the following functions related to; seeing, hearing, speaking, moving, breathing, and remembering or concentrating. Multiple general linear regression models were run to test the differences in amount of time of LPA and MVPA. Results: One in six young adolescents had disabilities. Young adolescents with functional limitations had 7 min.day −1 less LPA (p = 0.021) and 8 min.day −1 less MVPA (p = 0.011) than their peers without functional limitations. After controlling for gender, age, and device wear time, the differences in LPA among young adolescents with and without functional limitations were the same, however MVPA was no longer significantly less. Results varied according to different functional limitations. Conclusions: There were significant variations in physical activity behaviours by functional limitations and activity intensity. As such, tailored approaches to physical activity promotion may be dependent on understanding functional limitations as an indicator to disabilities.